1998
DOI: 10.1016/s0895-7061(97)00489-5
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Number in Arterial Hypertension Response to Treatment With Fosinopril or Atenolol

Abstract: Human insulin receptor (hINR) number and itsR esistance to insulin-mediated glucose disposal and compensatory hyperinsulinemia are common in arterial hypertension, occurring in approximately 50% of patients.1,2 The underlying mechanism, which has not yet been delineated, may include disturbances of insulin transport from plasma into the interstitial fluid, binding of insulin to its receptor (human insulin receptor, hINR), and the activity of a range of postreceptor signaling pathways. 3 The purpose of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Furthermore, the Rho-Rho-kinase pathway in the NTS was suggested to contribute to BP regulation via the sympathetic nervous system in vivo, suggesting that activation of this pathway is involved in the central mechanisms of hypertension (22). The first genetic association with human essential hypertension involved the IR gene (23,24). However, our results showed that the defect of insulin-mediated cardiovascular effects in the NTS of SHR was due to neither the suppression of the IR number ( Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, the Rho-Rho-kinase pathway in the NTS was suggested to contribute to BP regulation via the sympathetic nervous system in vivo, suggesting that activation of this pathway is involved in the central mechanisms of hypertension (22). The first genetic association with human essential hypertension involved the IR gene (23,24). However, our results showed that the defect of insulin-mediated cardiovascular effects in the NTS of SHR was due to neither the suppression of the IR number ( Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Abnormal placentation and placental vascular insufficiency decrease the concentration of angiogenic factor and increase the concentration of antiangiogenic factor, which results in abnormal angiogenesis and atherosclerotic changes associated with hyperinsulinemia [2][3][4] . Insulin concentrations affect the number of insulin receptors [4,5] . The number of insulin receptors expressed in erythrocytes is decreased during hypertension and the affinity of placental insulin receptors is low in women with pre-eclampsia [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Insulin concentrations affect the number of insulin receptors [4,5] . The number of insulin receptors expressed in erythrocytes is decreased during hypertension and the affinity of placental insulin receptors is low in women with pre-eclampsia [4][5][6] . On the other hand, a family history of preeclampsia is strong evidence of a genetic component [1,7] .…”
Section: Introductionmentioning
confidence: 99%